Kontribusi Dan Lokalitas Tafsir Faiḍ Al-Raḥmān - Syahid, Ahmad (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2020)
Nusantara's tafsir is understood as an interpretation product written by Nusantara scholars. There are things that are unique when we read the interpretations of Indonesian Ulama products. Among them, namely, the use of local languages, cultural elements and contexts that are specific to the Indonesian context. In general, after they perform the pilgrimage, they lived in Mecca-Arab for a long time to study religion over there, but their cultural identity and nationalism never disappeared. For example, Kiai Ṣaleh Darat who has a masterpiece in the form of interpretation, that is Faiḍ al-Raḥmān which will be explained in this article. The method used in this paper is descriptive analysis with a historical approach. The type of this research includes library research. The data sources are several libraries from books and journals describing Kiai Ṣaleh Darat. The result of this paper is a description of Kiai Ṣaleh Darat's intellectual history, the process of transmitting-transforming knowledge, its contribution to the thinking of the Nusantara’s Tafsir, and the locality of the interpretation of faidhur rahman.